Computational thinking proficiency among pre-service teachers at Universiti Putra Malaysia - Abdul Hamed, Ahmad Sarji; Wong, Su Luan; Abdul Rani, Mohd Zariat; Md Khambari, Mas Nida; Abd Rahim, Nur Aira; Khalid, Fariza; Jing, Teh Liang; Moses, Priscilla (I E E E Computer Society, 2024)
This paper investigates the computational thinking proficiency of pre-service teachers at the Faculty of Educational Studies, Universiti Putra Malaysia, through a multi-methods research design. The primary objective is to assess the understanding and perceptions of computational thinking among pre-service teachers and its implications for problem-solving proficiency in various academic disciplines. The study reveals that pre-service teachers possess above midpoint computational thinking proficiency. It emphasizes the importance of integrating computational thinking into teacher training programs to adequately prepare pre-service teachers for the digital era. The role of prior knowledge and experience in shaping computational thinking proficiency among individuals entering the teaching profession is highlighted. The findings underscore the necessity of incorporating computational thinking into teacher education curricula to meet the evolving demands of the digital landscape. Despite challenges related to varying levels of prior knowledge and limited exposure, there is a growing recognition of the significance of computational thinking in education. Teacher training initiatives are progressively integrating computational thinking into their programs, offering practical experiences and interdisciplinary approaches to empower pre-service teachers with essential proficiency for contemporary educational practices. Continuous learning and collaborative efforts are identified as crucial components in shaping the future of computational thinking in teacher education, ensuring educators remain at the forefront of educational advancements. Ultimately, the aim is to equip future generations with the computational thinking proficiencies necessary for navigating a dynamic and ever-changing world.